2021
DOI: 10.1055/s-0041-1731686
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrate Utilization in Children's Hospitals

Abstract: Prothrombin complex concentrates (PCCs) are used to manage bleeding in critically ill children. We performed a repeat cross-sectional study using the Pediatric Health Information System registry to describe PCC utilization in the U.S. children's hospitals over time and determine the relationship between PCC use and specific risk factors for bleeding. We included children < 18 years who received three-factor or four-factor PCC during hospital admission between January 2015 and December 2020 to describe the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Future randomized controlled trials should be utilized to establish effective doses for PCC in pediatric patients based on clinical and laboratory parameters, identify optimal protocols to define indications for PCC, define optimal laboratory parameters to evaluate clinical efficacy, and monitor for adverse effects. The need for such trials is demonstrated by the increasing off-label use of PCCs over the past 4 years in pediatric patients, especially in critically ill patients with a high risk for mortality [25].…”
Section: Pcc and Intracranial Pathologymentioning
confidence: 99%
“…Future randomized controlled trials should be utilized to establish effective doses for PCC in pediatric patients based on clinical and laboratory parameters, identify optimal protocols to define indications for PCC, define optimal laboratory parameters to evaluate clinical efficacy, and monitor for adverse effects. The need for such trials is demonstrated by the increasing off-label use of PCCs over the past 4 years in pediatric patients, especially in critically ill patients with a high risk for mortality [25].…”
Section: Pcc and Intracranial Pathologymentioning
confidence: 99%